Approach for the Direct Synthesis of β‐Dichlorosubstituted Acetanilides Using Iodine Trichloride (ICl3) as the Oxidant and Catalyst. Issue 4 (3rd April 2013) - Zhang, Qing; Liu, Weibing; Chen, Cui; Tan, Liquan
Abstract A reliable method for direct synthesis of β‐dichlorosubstituted acetanilides is reported. The key transformation involves the oxidative and catalytic cleavage of a carbon‐carbon bond in the presence of iodine trichloride (ICl3). In this protocol ICl3 is used not only as the catalyst but also as the oxidant which widely broadens the scope of its application in organic synthetic chemistry.